Minority stress and community connectedness among gay, lesbian and bisexual Australians: a comparison of rural and metropolitan localities - James S. Morandini; Alexander Blaszczynski; Ilan Dar‐Nimrod; Michael W. Ross (Elsevier, 2015)
Abstract Objective: To determine whether lesbian, gay and bisexual (LGB) Australians residing in rural‐remote and other non‐inner metropolitan localities experience increased levels of minority stress and reduced social support relative to their inner metropolitan counterparts. Methods: A convenience sample of (n=1306) LGB Australians completed an online survey that assessed minority stressors, level of connection with other LGB individuals and social isolation. Postcodes provided were coded into three metropolitan and two rural zones. A series of hierarchical regression analyses were undertaken to examine the effect of locality on minority stress and social support independent of sex, age, ethnicity, education and income. Results: Those residing in rural‐remote localities reported significantly increased concealment of sexuality from friends, more concern regarding disclosure of sexuality, less LGB community involvement, fewer friendships with other LGB people and, among men, higher levels of internalised homophobia than those residing in inner metropolitan areas. Unexpectedly, those residing in outer metropolitan areas of major cities experienced comparable levels of minority stress and LGB disconnection to those in rural and remote Australia. Conclusions: LGB individuals in rural‐remote and outer metropolitan areas of major cities face increased exposure to a number of minority stressors and less LGB community connectedness. These are risk factors associated with psychiatric morbidity in LGB populations. Implications: Health promotion targeted at reducing homophobia and discrimination in rural‐remote and outer metropolitan communities and additional services to assist LGB Australians struggling with stigma and isolation in non‐inner city areas may help mitigate the disadvantages faced by these LGB populations.